KOMUNIKASI PENYULUHAN BKKBN DALAM MENGIMPLEMENTASIKAN PROGRAM PENGELOLAAN UPPKA PADA KAMPUNG KB TUNAS HARAPAN PEKANBARU - Arif, Dinda Abdullah; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
BKKBN, as a non-ministerial state institution, is responsible for controlling population and family growth in Indonesia, which experiences a rapid growth rate every year. Pekanbaru is one of the cities in Riau Province with a high poverty rate that increases every year, which causes economic decline, living needs, and disruption of child nutrition (stunting). This is where the role of BKKBN Pekanbaru City is to overcome these problems through one of its programs, namely the Management and Guidance of Businesses to Increase the Income of Family Aspectors (UPPKA), carried out in the Tunas Harapan Family Planning Village Pekanbaru. The purpose of this research is to find out how the BKKBN extension communication process in implementing the UPPKA program works through the five stages of the innovation diffusion process, which is the theory in this study, namely knowledge, persuasion, decision, implementation, and confirmation. The research method used was descriptive-qualitative, where research informants were selected using purposive techniques. Data collection techniques were through observation, interviews, and documentation, which were then analyzed using the interactive model technique from Miles & Huberman, namely data reduction, data presentation, and conclusion drawing. The data validity checking technique uses an extension of participation and triangulation. The results showed that BKKBN's extension communication in implementing the UPPKA program in Tunas Harapan KB Village was through the knowledge of the spector families who were already quite good at the program; persuasion ran with a good process through the provision of tools and training; the content of the UPPKA program was a good reason for the spector families' decision to join the program; the implementation of extension communication was carried out through the implementation of the bazaar; and the benefits offered by the program were a confirmation for the spector families to continue to follow the program. Keywords: Extension Communication, Implementation, BKKBN